2020
DOI: 10.1002/ece3.6261
|View full text |Cite
|
Sign up to set email alerts
|

Impact of field‐realistic doses of glyphosate and nutritional stress on mosquito life history traits and susceptibility to malaria parasite infection

Abstract: Glyphosate is the world's most widely used herbicide. The commercial success of this molecule is due to its nonselectivity and its action, which would supposedly target specific biosynthetic pathways found mainly in plants. Multiple studies have however provided evidence for high sensitivity of many nontarget species to glyphosate and/or to formulations (glyphosate mixed with surfactants). This herbicide, found at significant levels in aquatic systems through surface runoffs, impacts life history traits and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…Mosquitoes were collected in the field and maintained in insectary under standard conditions (26 ± 1 • C, 70% ± 5% RH, and 12 h light/12 h dark photoperiod) since August 2017. In a previous study, we showed that the mosquito line used here was not resistant to imidacloprid (LC50: 30 µg/L; see [48]). Mosquito eggs used in this study were obtained by feeding 50 females on one healthy bird (Serinus canaria).…”
Section: Mosquito Rearing and Imidacloprid Exposurementioning
confidence: 70%
See 3 more Smart Citations
“…Mosquitoes were collected in the field and maintained in insectary under standard conditions (26 ± 1 • C, 70% ± 5% RH, and 12 h light/12 h dark photoperiod) since August 2017. In a previous study, we showed that the mosquito line used here was not resistant to imidacloprid (LC50: 30 µg/L; see [48]). Mosquito eggs used in this study were obtained by feeding 50 females on one healthy bird (Serinus canaria).…”
Section: Mosquito Rearing and Imidacloprid Exposurementioning
confidence: 70%
“…We observed no effects of this pesticide on any of the parameters examined in this study. Based on the analysis of survival rates of Culex pipiens larvae 72 h after exposure to different doses of imidaclopird, we demonstrated in a previous study that the mosquito line used in this experiment was not resistant to this pesticide (concentrations of imidaclopird that kills 50% of the test animals (LC 50 ): 30 µg/L, see [48]). The fact that no effect was observed in the present study is probably explained by the low concentrations of imidacloprid used (3 µg/L in water and 0.8 µg/Kg in sugar solution).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the interactions between pathogens and mosquitoes may be determined by the presence of pollutants derived from human activities. Culex pipiens larvae fed a standard diet had higher avian Plasmodium prevalence when exposed to the herbicide glyphosate [ 136 ]. In addition, antibiotics, and other personal care products in waters in which mosquitoes breed may affect mosquito development and the epidemiology of mosquito-borne pathogens [ 137 ].…”
Section: Effects Of Landscape Change On West Nile Virus and Avian Plasmodiummentioning
confidence: 99%